Timing of Intubation in COVID-19: When It Is Too Early and When It Is Too Late. (13th February 2023) - Grotberg, John C.; Kraft, Bryan D.
Abstract : The timing of initiating mechanical ventilation in patients with acute respiratory distress syndrome due to COVID-19 remains controversial. At the outset of the pandemic, "very early" intubation was recommended in patients requiring oxygen flows above 6 L per minute but was followed closely thereafter by avoidance of invasive mechanical ventilation (IMV) due to a perceived (yet over-estimated) risk of mortality after intubation. While the use of noninvasive methods of oxygen delivery, such as high-flow nasal oxygen (HFNO) or noninvasive positive pressure ventilation (NIV), can avert the need for mechanical ventilation in some, accumulating evidence suggests delayed intubation is also associated with an increased mortality in a subset of COVID-19 patients. Close monitoring is necessary in COVID-19 patients on HFNO or NIV to identify signs of noninvasive failure and ensure appropriate provision of IMV.